Intermediate and Long-Term Outcomes of Glaucoma Drainage Device Implantation by Glaucoma Fellows at a Tertiary Eye Center - Cris Martin P. Jacoba, MD; John Mark S. de Leon, MD, DPBO (Philippine Journal of Ophthalmology)
Objective: To describe surgical outcomes of glaucoma drainage device (GDD) implantation performed by glaucoma fellows, and to identify factors influencing success.